Mechanisms and kinetic modelling of steam gasification of brown coal in the presence of volatile–char interactions - kajitani, Shiro; Tay, Hui-ling; Zhang, Shu; Li, Chun-Zhu (Elsevier Science Ltd, 2013)
It is known that Victorian brown coal has higher reactivity for gasification because of catalysis of inherent AAEMspecies than high-rank coal. However, the experimental results of steam gasification of brown coal in a fluidised-bed/fixed-bed reactor at 800 C have suggested that the inhibitory effects of the volatile–char interactions on char gasification are not negligible. The mechanisms and kinetics model of the char gasification and volatile–char interactions were discussed to describe quantitatively the inhibition of char gasification by volatiles, in this study. The elementary reactions of the char gasification and volatile–char interactions, which are consist of the adsorption of free radicals from volatiles, the volatilisation of catalyst and the evolution of char structure affected by radicals from volatiles, were proposed. The L-H type reaction rate equations for brown coal gasification were determined, and the kinetics model was verified by the comparison with several series of experiments. The proposed kinetics model described the experimental results of the coal conversions and the concentrations of Na in char during steam gasification very well. This kinetics model would be useful in designing any industrial fluidised-bed gasifier for low-rank fuels and estimating their performance.